(untitled) - FAO (Rome, 1997)
Among the limiting factors to cotton production in the Near East is seasonal pest infestation. Cotton is subject to attack from more than 20 economically importan arthropod pests, 12 disease agents and 22 noxious weeds. This mean that cotton protection measures have to be taken. In most cases, pesticide use has been the sole method used for cotton protection in Near Eastern countries, but this has resulted in complications such as pesticide residues in cotton, pest resistance to pesticides, the emergence of previously minor pests as major pests, disturbances in the natural balance, pesticide poisoning and high cotton production costs.
Keywords: cotton,plant, protection of